Coral Reef Restoration Project and Impact on the Life of the Community of Bontosua Island South Sulawesi Island - Mansyur Radjab; Suparman Abdullah; Sultan Sultan; Suryanto Arifin; Ridwan Syam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze its impact on individual, household and community income, analyze its impact on political life or leadership and punggawa-sawi relations, and analyze institutional impact as a means of supporting coral reef restoration programs. The research method used is descriptive qualitative research with data collection through in-depth interviews with deliberately selected informants, namely village heads, non-government officials and members of the fishing community. In addition, he also observed several coral reef restoration project activities and local community activities. The results show that the coral reef restoration program that has been running for approximately four years as a transition has not yet had an impact on improving the economy of residents, individuals or groups or communities, both in terms of income, especially capital. Coral reef restoration is still in the maintenance/monitoring program stage, so fishing around the reef restoration area is still prohibited. The perceived impact may be limited to salary/incentives. When talking about politics or leadership and punggawa-sawi relations, some people feel that the hopes that were previously raised have become empty for some people. what people feel now is gone, just like what they felt before. The program tends to be used as a source of political capital. The group in question has the nuances of selective slashing, who is close to the Village Head, he is the one who is involved. As for the fishermen's institutions, especially the retainer-sawi relationship, it is said that they do not know exactly what it is. The impact on the survival of organizations involved in coral reef restoration is the Community Monitoring Post (Poswasmas), which is a participatory organization, but in practice tends to be limited to the interests of fishermen.